A balanced whole arm reciprocal translocation resulting in three different adverse pregnancy outcomes. Issue 5 (May 1993) - Cooper, P J; Towe, C; Crolla, J A
Abstract : A family with a whole arm translocation t(13;18)(13p18p;13q18q) was ascertained through a stillbirth with clinical features suggestive of trisomy 18. Two subsequent pregnancies both spontaneously aborted; one was found to have a 69, XXX, t(13;18)mat chromosome constitution while the other had a 45, XY, -13, -18, + der(18)t(13;18)mat chromosome constitution.